Injury Pattern as an Indication of Seat Belt Failure in Ejected Vehicle Occupants. Issue 5 (25th March 2014) - Freeman, Michael D.; Eriksson, Anders; Leith, Wendy
Abstract Prior authors have suggested that when occupant ejection occurs in association with a seat belt failure, entanglement of the outboard upper extremity (OUE) with the retracting shoulder belt will invariably occur, leaving injury pattern evidence of belt use. In the present investigation, the authors assessed this theory using data accessed from the NASS‐CDS for ejected front seat occupants of passenger vehicles. Logistic regression models were used to assess the associations between seat belt failure status and injuries. Injury types associated with seat belt failure were significant OUE and head injuries (OR = 3.87, [95% CI 1.2, 13.0] and 3.1, [95% CI 1.0, 9.7], respectively). The two injury types were found to be a predictor of seat belt use and subsequent failure only if combined with a high (≥0.8) precrash probability of belt use. The injury pattern associated with a seat belt failure‐related ejection has limited use in the forensic investigation of crash‐related ejections.